"The great divide": skill gap between the employer's expectations and skills possessed by employees. Issue 4 (3rd April 2017) - Malik, Geetika; Venkatraman, A.
Abstract : Purpose: The purpose of this paper is to emphasise on demand supply skill gap of human resources in India which would help generate reasons for the same and the necessary steps to be taken to improve the situation and bridge the skill gap helping maximum number of the students becoming employable. It will put an impact on various stakeholders about the steps to be taken in bridging the gap in India. Design/methodology/approach: A review of available literature was done in order to understand the reasons behind the increasing skill gap despite a vibrant and abundance of young population. Findings: The findings of the paper implicitly point out that a vast skill gap is prevailing in the Indian labour market and there is a dearth of human intellectual capital in India. Also it emphasises on the role of various stakeholders in bridging the skill gap by investing in workforce of today for a better tomorrow. Originality/value: Based on literature review, the paper makes specific recommendations to various stakeholders (industry, academia, and government) in bridging the skill gap and would serve as a roadmap for companies guiding them to follow certain strategies to improve skills of future workers by investing in them and growing their own talent pool; and is an attempt to highlight the fact that India's jobless growth is not going to reap the demographic dividend and certainly the increasing skill gap needs to be bridged ASAP.